UPAH BURUH KARYAWAN DITINJAU MENURUT HUKUM ISLAM DAN HUKUM POSITIF (Studi di Disnaker Kabupaten Pidie) - Safriadi Safriadi (Jurnal Tahqiqa : Jurnal Ilmiah Pemikiran Hukum Islam, 2018)
Minimum wage is an important element in Indonesia's social policy. Whatis typical in systems developed in Indonesia is the emphasis on wageproportionality, which is the practice of attributing wages to the needs of workers.The legal basis of the current minimum wage determination can be found in theprovisions of Article 88 paragraph (4) of Law Number 13 of 2003 concerningManpower and Regulation of the Governor of Aceh Number 60 of 2015concerning the determination of the minimum wage of Aceh Province. However,in Pidie district, the implementation of workers' wages is not in accordance withthe regulation. So that the implementation of wages on employees is not inaccordance with it properly. The purpose of this research is to know and explainthe legal arrangement to the provision of wage labor according to Islamic law andpositive law of Indonesia and explain the implementation of wage for workers inthe Office of Manpower of Pidie Regency, and explain the Differences of IslamicLaw And Positive Law in the provision of wages. This research uses normativeand sociological juridical research methods. Normative research uses secondarydata, while sociological research uses primary data obtained from the field. Thelegal arrangement of payment of wages according to Islamic law is regulated inthe Qur'an and Hadith concluded that basically the issue of wages is not only amatter related to money and profit but rather on the issue of how we understandand respect others and help between the one with the other. While the regulationof wages in the positive law on wages for the government workforce has made thesigns in Law No. 13 of 2003 on employment. In addition, it has also been madePresidential Decree no. 107 of 2004 on Wage Council, Decree of the Minister ofManpower and Transmigration NoKEP-231 / MEN / 2003. Implementation ofWages for Workers in Pidie District Manpower Office does not refer to AcehGovernor Regulation No. 60 of 2015 concerning the determination of minimumwage of Aceh Province. In because if it refers to the governor's regulation has thedisadvantages and advantages that if the Province Minimum Wage to bedetermined, then the workers / laborers whose domicile is adjacent or borderedbetween districts / cities will not occur gap. Wherever the worker / laborer in onecompany will apply the same Minimum Wage. The Differences of Islamic LawAnd Positive Laws In Rewarding Wages are decent wages in the positive lawmost of which are tangible money, only a fraction of wages can be in the form ofmoney, in accordance with the employment agreement. Whereas in Islamic lawthe form of wages is not always the form of money, the wage can be anything.The timing of payment of wages in positive law can be postponed or suspendedfor some reason, as companies are threatened with bankruptcy. In Islamic law thewage payment deduction can reduce the value of worthiness. Nominal decentwage in positive law is to look at provincial minimum wage. The rule is the minimum standard in determining wages. While in Islamic law does not mention.In Islam only gives signs in determining wages based on the value of wages itself.The minimum wage as a reasonable wage-size limit should not be accompaniedby the rule of allowance of wage deferral, this is contrary to other regulations.Strange if wages are minimum and can be suspended which will reduce the valueof worthiness. In addition, it is recommended that wages in positive law pay moreattention to the families of workers and other needs. It is in accordance withIslamic principles.